Application of FT-NIR spectroscopy and FT-IR spectroscopy to Chinese rice wine for rapid determination of fermentation process parameters. Issue 6 (21st March 2015) - Wu, Zhengzong; Long, Jie; Xu, Enbo; Wu, Chunsen; Wang, Fang; Xu, Xueming; Jin, Zhengyu; Jiao, Aiquan
<x xml:space="preserve">Abstract</x> NIR and MIR combined with chemometric tools were used to monitor time-related changes during Chinese rice wine fermentation.